Analysis of Non-Physical Waste Production Variables (Lean Six Sigma) on Project Time Management Through the Mediation of Lean Construction - Rakhmad Sugih Hartono; Slamet Riyadi; Fausta Ari Barata (Green Publisher Indonesia, 2025)
Construction projects are entering an era of profitability, aiming to achieve business goals with minimal resources. Yet, prior research shows only 54% complete on time, due to activity variations causing production waste and delays. This study examines non-physical waste production from the Lean Six Sigma concept's influence on project time management via Lean Construction mediation in the PUSRI 3B project. Methods included identifying delay factors from literature and field observations, categorizing them as Lean Six Sigma non-physical waste, and distributing Likert-scale questionnaires to respondents. Data were analyzed using SmartPLS ver. 4 with Structural Equation Modeling (SEM). Results indicate defect and overproduction waste significantly affect Lean Construction implementation but not time management—present in PUSRI 3B yet mitigated by quality control, avoiding delays. Inventory waste significantly impacts both Lean Construction and time management, contributing to delays. Overall, non-physical waste production significantly influences time management through Lean Construction mediation.